2010
DOI: 10.1353/sof.2010.0082
|View full text |Cite
|
Sign up to set email alerts
|

Legal Status and Wage Disparities for Mexican Immigrants

Abstract: This paper employs a unique method of imputing the legal status of Mexican immigrants in the 1996-1999 and 2001-2003 panels of the Survey of Income and Program Participation to provide new evidence of the role of legal authorization in the U.S. on workers’ wages. Using growth curve techniques, we estimate wage trajectories for four groups: documented Mexican immigrants, undocumented Mexican immigrants, U.S-born Mexican Americans, and native non-Latino whites. Our estimates reveal a 17 percent wage disparity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
165
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 16 publications
(30 reference statements)
7
165
1
Order By: Relevance
“…On the other hand, there are also reasons to believe that DACA may increase college dropout rates for undocumented students. Nearly 70% of families headed by undocumented parents subsist at or near the poverty line (Amuedo-Dorantes and Antman 2016; Gonzales, Terriquez and Ruszczyk 2014) and are typically employed in low-wage, unstable jobs that offer no benefits like health insurance, sick leave or over-time pay (Donato et al 2008;Hall, Greenman and Farkas 2010). Thus, families headed by undocumented parents commonly rely on all working-age members to contribute to family income.…”
Section: Deferred Action For Childhood Arrivals and Higher Educationmentioning
confidence: 99%
“…On the other hand, there are also reasons to believe that DACA may increase college dropout rates for undocumented students. Nearly 70% of families headed by undocumented parents subsist at or near the poverty line (Amuedo-Dorantes and Antman 2016; Gonzales, Terriquez and Ruszczyk 2014) and are typically employed in low-wage, unstable jobs that offer no benefits like health insurance, sick leave or over-time pay (Donato et al 2008;Hall, Greenman and Farkas 2010). Thus, families headed by undocumented parents commonly rely on all working-age members to contribute to family income.…”
Section: Deferred Action For Childhood Arrivals and Higher Educationmentioning
confidence: 99%
“…Extensive research indicates that lacking legal status disadvantages unauthorized Latino immigrants in accessing employment-based benefits such as health insurance, post-baccalaureate educational opportunities, housing affordability, and other outcomes (e.g., Chavez, 1996;Marcelli, 2004;Goldman et al, 2005;Abrego, 2006;Hall et al, 2010;McConnell, 2013). Studies further document that unauthorized immigrants earn lower incomes than authorized immigrants (e.g., Rivera-Batiz, 1999;Bratsberg et al, 2002;Aguilera and Massey, 2003;Hall et al, 2010;Flippen, 2012).…”
Section: Legal Statusmentioning
confidence: 99%
“…Studies further document that unauthorized immigrants earn lower incomes than authorized immigrants (e.g., Rivera-Batiz, 1999;Bratsberg et al, 2002;Aguilera and Massey, 2003;Hall et al, 2010;Flippen, 2012). In fact, a review of the literature reveals that unauthorized immigrants, especially from Latin America, experience little upward mobility despite decades of U.S. residence and other indicators that typically suggest immigrant incorporation (Donato and Armenta, 2011).…”
Section: Legal Statusmentioning
confidence: 99%
“…Studies have also detailed how unauthorized status inhibits workers' ability to file claims against their employers when faced with workplace rights abuses (Gleeson 2010(Gleeson , 2012. Finally, Hall, Greenman, and Farkas (2011) found that unauthorized workers do not reap the same rewards for schooling and their wages grow more slowly in comparison to their authorized counterparts.…”
mentioning
confidence: 99%